INTEGRASI TAM DAN ECM DALAM MENJELASKAN NIAT MEMBELI KEMBALI PRODUK FASHION SECARA ONLINE DI KOTA DENPASAR - Dewi, Ayu Prasetya; Yasa, Ni Nyoman Kerti; Setiawan, Putu Yudi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study is to explain integration TAM and ECM that influence the online repurchase intention. The sample used as many as 130 respondents its taken using purposive sampling that live in the city of Denpasar, and ever make online purchases to fashion products Data Analyzed using Structural Equation Model (SEM). The results of this study indicate the construct of perceived ease of use and construct confirmation has a positive and significant impact on the perceived of usefulness. Perceived of usefulness  also has a positive and significant impact on online repurchase intention. The implication of this study shows that consumers want a system that is easy to understand, flexible to use so that processes transactions on the online shopping can be faster Suggested for online businesses for more attention to the quality of the site and continue to make enhancements to the navigation system and the menus are easy to use in the site, so that consumer perceived of usefulness can be established and furthermore consumers willing to online repurchase .
Keywords: TAM, ECM, perceived ease of use, confirmation, perceived usefulness, online repurchase intention.